A fractional model of supercapacitors for use in energy storage systems of next-generation shipboard electrical networks. Issue 4 (2nd February 2017) - Kopka, Ryszard; Tarczyński, Wiesław
Abstract : The reduction of energy consumption and carbon dioxide emission has forced designers and manufacturers to develop new, more efficient ship propulsion systems. Traditional mechanical systems are replaced by hybrid or completely electric ones. In addition to the combustion, the electromechanical sources are considered. But in such small electric grids, in order to reduce the impact of load fluctuations on the power system, energy storage devices are proposed. Such devices are able to supply a peak power. As examples the batteries, flywheels, but primarily supercapacitors can be considered. Unfortunately, a very low voltage causes supercapacitors to work in stacks. This paper presents the results of analysis of the influence of changes in selected supercapacitor parameters changes on its terminal voltage during the cycles of charging and discharging. The model parameters are estimated based on the test measurements, while the differ-integral calculus of fractional order is used to derive the model output. It turns out that such an approach provides a very good fit for model responses even for its very simple structures. In addition, a very precise mathematical model allows to accurately estimate an amount of stored energy and estimate the supercapacitor reliability.